Primary dysmenorrhea and its associated factors among female high school students in Nekemte town, East Wallaga Zone, Western Oromia, Ethiopia: a cross-sectional study - Gindaba, Bekan Gudata; Abera Gudeta, Tesfaye; Sebu, Lemane Dereje; Zerihun Gindaba, Ebisa; Abdisa, Misgana Tesgara (Frontiers in Reproductive Health, 2025)
BackgroundPrimary dysmenorrhea is a common gynecological problem characterized by recurrent, periodical, and cramping pain in the lower abdomen that occurs before or during menstruation, usually without pelvic disease. Its magnitude has not been well studied; some of the associated factors are inconclusive. Therefore, the goal of this study was to fill gaps on the magnitude, and associated factors of primary dysmenorrhea among female high school students in Nekemte town.ObjectivesTo assess the magnitude of primary dysmenorrhea, its associated factors among high school students in Nekemte town, East Wallaga, Western Oromia, Ethiopia, 2023.MethodsAn institutional-based cross-sectional study was conducted among high school students in Nekemte town from June 05 to 19, 2023. The calculated total sample size was 534, and data were collected from four governmental high schools and one private high school that were selected by multistage stratified sampling. The collected data were entered into Epi Info version 3.1 and analyzed using SPSS version 25. Binary and multivariable logistic regressions were used to find associations between dependent and independent variables.ResultsThe magnitude of primary dysmenorrhea was 68.4% (95% CI = 64.3%, 72.0%). Anxiety (AOR = 2.41, 95% CI = 1.31, 4.43), family history of primary dysmenorrhea (AOR = 4.64, 95% CI = 2.74, 7.86), sexual intercourse (AOR = 0.34, 95% CI = 0.21, 0.55), drinking tea <4 cups per day (AOR = 0.38, 95% CI = 0.22, 0.60), and physical activity (AOR = 0.06, 95% CI = 0.03, 0.11) were factors associated with primary dysmenorrhea.ConclusionThe magnitude of primary dysmenorrhea was high among high school students in the study area. Sexual intercourse, physical activity, drinking tea, anxiety, and family history of primary dysmenorrhea were significantly associated with primary dysmenorrhea.